SOCIAL MEDIA INFLUENCERS AND DATA PRIVACY: LEGAL OBLIGATIONS AND RESPONSIBILITIES (SCIENCE TIME JOURNAL, 2024)
This article explores the legal duties and liabilities that social media influencers have when it comes to data privacy. The increasing impact of social media has sparked considerable worries regarding the collection, utilization, and safeguarding of personal information. This research examines existing laws, rules, and scholarly studies to offer a thorough comprehension of the legal environment that influencers need to navigate. The main concern is making sure that influencers follow data privacy laws to safeguard the personal information of individuals.